Biocommercial characteristic of the Gulf of Riga eel - Kairov, E.A.; Rimsh, E.Ya. (Baltijskij Nauchno-issledovatelskij Institut Rybnogo Khozyajstva, 1979)
The results of biological research conducted on eel in the Gulf of Riga in 1974-1975 are presented in the article. Data characterizing the condition of its fishery both at present and in pre-war and post-war years are examined. The characteristic of length-weight and age composition of the Gulf of Riga eel is given. The reasons of its stocks decrease for the last two decades (60-70ies) are analyzed and the possibility of intensification of the eel fishery in the regions of the western coast of the Gulf of Riga due to a specialized fishing arrangement is grounded. Published Not Known